1999
DOI: 10.1093/emboj/18.17.4779
|View full text |Cite
|
Sign up to set email alerts
|

The nucleosomal response associated with immediate-early gene induction is mediated via alternative MAP kinase cascades: MSK1 as a potential histone H3/HMG-14 kinase

Abstract: The nucleosomal response refers to the rapid phosphorylation of histone H3 on serine 10 and HMG-14 on serine 6 that occurs concomitantly with immediateearly (IE) gene induction in response to a wide variety of stimuli. Using antibodies against the phosphorylated residues, we show that H3 and HMG-14 phosphorylation is mediated via different MAP kinase (MAPK) cascades, depending on the stimulus. The nucleosomal response elicited by TPA is ERK-dependent, whereas that elicited by anisomycin is p38 MAPK-dependent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
414
0
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(440 citation statements)
references
References 87 publications
20
414
0
5
Order By: Relevance
“…Our studies demonstrate that PD 98059, an inhibitor of MEK and consequently of ERK, largely suppresses the activation of endogeneous p-MSK1 by quercetin, while H-89, an inhibitor of MSK, does not suppresses this activation ( Figure 9B). It has been shown that the inhibitor of MSK1, H-89, affects only the activity of the kinase but not its phosphorylation levels [30]. Consistent with these findings, MSK1 can be activated by ERK in vitro (Figure 9).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our studies demonstrate that PD 98059, an inhibitor of MEK and consequently of ERK, largely suppresses the activation of endogeneous p-MSK1 by quercetin, while H-89, an inhibitor of MSK, does not suppresses this activation ( Figure 9B). It has been shown that the inhibitor of MSK1, H-89, affects only the activity of the kinase but not its phosphorylation levels [30]. Consistent with these findings, MSK1 can be activated by ERK in vitro (Figure 9).…”
Section: Discussionsupporting
confidence: 75%
“…Although there are reports on the interaction between survivin and caspases 3, 7, and 9, others have failed to demonstrate a direct effect on these proteases [30,31]. One of the important features for TRAIL treatment to be effective is that the cancer cells must be sensitive to the effects of TRAIL to prevent emerging TRAIL resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In each case increased H3 phosphorylation was found to occur at particular genes activated by these pathways which suggests a role in regulation of gene expression [11][12][13][14][15]. Kinases shown to play important roles in the regulation of H3 phosphorylation at serines 10 and 28 include MSK1/2 [16,17], IKKα [12,13] and aurora kinases (mitotic phosphorylation) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, the phosphorylation of histone H3 at its basic N-terminal tail was rapidly increased in response to growth factors, phorbol esters, okadiac acid, and protein synthesis inhibitors. The dynamics of histone phosphorylation are correlated with the transcriptional induction of proto-oncogenes, c-fos and c-jun, suggesting histone phosphorylation might play a role in gene expression as well (Mahadevan et al, 1991;Thomson et al, 1999b). The identification of RSK-2 (ribosomal S6 kinase -2) and MSK1 (mitogen and stress activated kinase 1) and the discovery that these protein kinases are involved in histone H3 SerlO phosphorylation greatly forwarded the understanding of the histone H3 SerlO phosphorylation signal transduction pathways that lead to gene expression (Deak et al, 1998;New et al, 1999;Sassone-Corsi et al, 1999).…”
Section: Histone Modifications That Regulate Chromatin Structure and mentioning
confidence: 99%
“…The lack of SerlO phosphorylation in these fibroblasts could be restored by an RSK-2 transgene (Sassone-Corsi et al, 1999), suggesting RSK-2 is required for the EGF induced H3 SerlO phosphorylation in vivo. Moreover, MSK1 can be activated by both mitogen and stress signals and was proposed to mediate H3 SerlO phosphorylation and hence lead to the expression of immediate early genes c-jun and c-fos (Thomson et al, 1999a;Thomson et al, 1999b).…”
Section: Histone Modifications That Regulate Chromatin Structure and mentioning
confidence: 99%